2007
DOI: 10.1111/j.1528-1167.2006.00971.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Self‐reported Quality of Life between Patients with Epilepsy and Neurocardiogenic Syncope

Abstract: Summary: Epilepsy and neurocardiogenic syncope share a final common pathway of loss of consciousness and consequent social disruption. We compared 52 patients with syncope, 96 with epilepsy and 100 controls. Epilepsy and syncope patients expressed significantly higher levels of anxiety and depression and reported significantly less good quality of life (QoL) compared with controls. There were no significant differences on any of the QoL parameters measured between the syncope and epilepsy patients. These findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 13 publications
0
29
0
Order By: Relevance
“…QoL is reduced with recurrent syncope, [725][726][727][728][729][730][731][732][733] as demonstrated in studies that compared patients with and without syncope. 727,731 QoL associated with recurrent syncope was equivalent to severe rheumatoid arthritis and chronic low-back pain in an adult population.…”
Section: Impact Of Syncope On Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…QoL is reduced with recurrent syncope, [725][726][727][728][729][730][731][732][733] as demonstrated in studies that compared patients with and without syncope. 727,731 QoL associated with recurrent syncope was equivalent to severe rheumatoid arthritis and chronic low-back pain in an adult population.…”
Section: Impact Of Syncope On Quality Of Lifementioning
confidence: 99%
“…727,731 QoL associated with recurrent syncope was equivalent to severe rheumatoid arthritis and chronic low-back pain in an adult population. 728 Similarly, pediatric patients with recurrent syncope reported worse QoL than individuals with diabetes mellitus and equivalent QoL to individuals with asthma, end-stage renal disease, and structural heart disease.…”
Section: Impact Of Syncope On Quality Of Lifementioning
confidence: 99%
“…Patients with NCS report worse QOL and experience higher levels of anxiety, depression and somatization disorders than control populations [23,24]. The level of impairment is similar to severe arthritis, pain, epilepsy and other chronic disorders.…”
Section: How and Why Are Patients Impaired?mentioning
confidence: 70%
“…This time before the patient is completely "back to normal", represents a period of altered conscious state. In a study which compared the self-reported QoL of patients with epilepsy to the QoL of patients with cardiogenic syncope [52], both epilepsy and syncope patients reported their QoL to be impaired to a similar degree, with no significant differences on any of the individual QoL parameters. As many forms of epilepsy and cardiogenic syncope share a final common path of consciousness impairment, these findings suggest that the unpredictable alteration of conscious states may be one of the main contributors to poor QoL, at least in a large subset of patients with epilepsy.…”
Section: Assembling the Pieces Of The Puzzle: Epilepsy Consciousnessmentioning
confidence: 99%
“…Epilepsy can profoundly affect many aspects of Quality of Life (QoL) [4]. Patients with epilepsy have poorer QoL than people without epilepsy or people with chronic illnesses other than epilepsy [52,60,62,65]. A key feature of epilepsy is its ability to alter the conscious states of the patients during seizures.…”
Section: Introductionmentioning
confidence: 99%